Response to PD-1 inhibitor after progression on PD-L1 inhibitor in advanced HCC. Issue 8 (12th August 2022) - Cerniglia, Michael; Klepadlo, Michal; Sheneman, David; Kim, Sunnie S
Abstract : For hepatocellular carcinoma, the IMbrave150 trial demonstrated that combination atezolizumab and bevacizumab had significantly better overall survival compared with sorafenib in patients with unresectable disease. However, as more immune checkpoint inhibitors are approved as first-line agents in gastrointestinal cancers, there have been few reports on whether sequential PD-1/PD-L1 blockade is beneficial in the treatment of these diseases. We present a patient with hepatocellular carcinoma who had disease progression on atezolizumab, a PD-L1 inhibitor, but subsequently had a remarkable response to pembrolizumab, a PD-1 inhibitor.